Analisis Efektivitas dan Efisiensi PDAM Kota Mojokerto - Nekky Rahmiyati; Sri Andayani (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2014)
Abstract: This research was done in PDAM Mojokerto city. This PDAM is a company which monopolizes the water supply to public so that it can supply and distribute water according to the public weeds.The problems in this research are : a. How is efficiency the performance rate analysis result of PDAM as one of BUMD in Mojokerto city ?. b. How is the effectivity performance of PDAM as water supplier for public in Mojokerto city? The purpose is to analyze the performance efficiency rate of PDAM as one of BUMD in Mojokerto city, and for knowing the performance effectivity of PDAM Mojokerto city.The research result of ROE (Return on Equity) PDAM always get loss increasingly. Cash ability for paying the short debt is very low.The collection of receivable in the year of 2010 increased 32.325,760, in the 2011 increased 18.337,450, in the year of 2012 increased 73.819,330., this showed that there was receivable abundant and there was no effective collect receivable, while in the year 2013 there was better collect compared to the previous year. The soluability ratio increased in the year 2009 with the amount 3.63% that meant every debt of one unit would be guaranted 3,63 unit asset and in the year 2010 with the amount of 4,20%. In the year 2011 would be 6,16% in the year 2012 with the amount 5,52%, in the year 2013 in 13,06%. Based on the result of performance effectivity PDAM Mojokerto city, it is still not effective. We can see from the ratio of the population with customer, the rate of water loos is about 50% and water quality and water wetae also the were so many complaints, showed that there is still not effective the PDAM performance Mojokerto city. The recommendation of PDAM Mojokerto city must work harder to increase the performance efficiency and effectivity.Keywords: performance efficiency and effectivity.